Effects of Suryanamaskara and Sheetali Pranayama on College Students Aggression: A Prospective Interventional Study - Youganjaly Mehra; Malika Sharma; Kalpana Sharma (Journal of Clinical and Diagnostic Research)
Introduction: Students today face a more fast-paced and demanding lifestyle due to heavy workloads and hectic schedules. By using the potential of Suryanamaskara, a dynamic sequence of yoga postures known for its energising and calming effects, along with Sheetali Pranayama, a cooling breathing technique that promotes relaxation and reduces stress, this study contributes to the growing body of research on non pharmacological interventions for emotional regulation in adults. The focus of this research is the effects of Suryanamaskara and Sheetali Pranayama on reducing aggression levels in college students. Aim: To investigate the effects of Suryanamaskara and Sheetali Pranayama in reducing aggression levels in college students. Materials and Methods: This prospective interventional study employed a stratified purposive random sampling design to evaluate the efficacy of Suryanamaskara and Sheetali Pranayama in reducing aggression levels among college students. Voluntary participants were initially screened using the Buss and Perry Aggression Questionnaire (AQ) and those who exhibited high aggression scores were selected for the intervention training programme. A total of 54 participants were randomly assigned to two experimental groups. Group 1 underwent a Suryanamaskara intervention, while Group 2 engaged in Sheetali Pranayama, both incorporating Sukshma Vyayama and a cooling down period within the framework. Intervention sessions lasted 45 minutes, five days a week, for 10 weeks. Aggression levels were assessed pre- and postintervention and paired sample t-tests and independent sample t-tests were used for statistical analysis. Results: The findings of this study demonstrate a significant reduction in aggression levels among college students following a 10 week yoga intervention programme, with the mean difference in aggression scores between pre- and postintervention being 14.40 for the Suryanamaskara group and 17.29 for the Sheetali Pranayama group, indicating a decrease in aggression levels. Both the Suryanamaskara and Sheetali Pranayama groups exhibited notable improvements in aggression scores as measured by the Buss and Perry AQ. However, a comparative analysis using independent sample t-tests and effect size showed that the pretest t-statistics were -1.59 (p-value=0.11) and for the post-test t-statistics were -1.16 (p-value=0.24), revealing no significant differences between the groups for either pretest or post-test scores (p-value>0.05). Conclusion: This experimental study demonstrated a significant reduction in aggression levels among college students following a 10-week intervention with either Suryanamaskara or Sheetali Pranayama programmes. A comparative analysis revealed equivalent changes in aggression levels between the two groups, indicating that both yogic interventions were equally effective in reducing aggression in college students.